Peningkatan Pemahaman Angka Puluhan Bahasa Inggris dengan Metode Inovatif pada Siswa SD 173632 - Ike Nurmayanti Sipahutar; Vincentius Mikael Lumban Toruan; Roberto Panggabean; Elfri Ika Hutauruk; Josua Sihombing (Jurnal Pelayanan Masyarakat, 2025)
This community service aims to improve the understanding of grade 4 students of SDN 173632 Parparean III, Porsea in learning nominal tens in English. There are still many elementary school students who have difficulty in recognizing, pronouncing, and writing tens in English correctly. This problem can hinder the development of their basic English skills, especially in terms of counting and daily conversation. To overcome these problems, this community service activity implements an innovative learning method that combines educational games, visual media, and interactive pronunciation techniques. The goal is to create a fun learning atmosphere and motivate students to actively participate in the learning process. The approach used is Classroom Action Research (CAR), with data collection through direct observation, short interviews with class teachers, and oral comprehension tests before and after the intervention. The results of the observation showed a significant increase in students' ability to understand and use tens in English after the method was applied. Thus, this learning method has proven effective and can be used as a reference or alternative strategy in teaching English at the elementary school level, especially for numbers and figures.